Persistent left superior vena cava detected following central venous catheter placement - Karen Makhoul; Peter Makhoul; Ahmad Zaghal (Elsevier, 2021)
Persistent left superior vena cava (PLSVC) is the most common congenital anomaly of the SVC. In most cases, the PLSVC drains via the coronary sinus into the right atrium, but in some cases, it drains into the left atrium instead. This anomaly is of particular importance during central venous catheter (CVC) placement, especially during a left-sided approach, as manipulation within the coronary sinus has been associated with hemodynamic instability and shock. PLSVC is usually suspected when confirmatory plain radiograph shows the catheter traveling along the left mediastinal border. We are reporting the case of a 3-year-old female patient with CVC placement into her left subclavian vein and subsequently a PLSVC. Portable chest radiography showed the catheter coursing along the lateral border of the left mediastinum. An echocardiogram showed flow from the subclavian vein into the right atrium; therefore, the catheter most likely terminated in a PLSVC draining into the right atrium. The catheter had excellent flow and was kept in place for six days without any complications or sequelae before it was removed.